APPLICATION OF VALUE ENGINEERING IN THE CONTRUCTION OF CAMPUS III UIN MALANG. (Case Study : Engineering Lecture Building 02) - Wahyu Zaena Akmala; Radhia Jatu Noviarsita (Jurusan Teknik Sipil Politeknik Negeri Malang, 2026)
In the construction project of campus III of UIN Malang, Engineering Lecture Building 02, efficiency and management related to construction costs. One of them is the business by applying Value Engineering (VE) The data used is the Budget Plan (RAB), Work Plan and Work Plan and Terms (RKS), Labor Unit Price Analysis (AHSP) by carrying out stages starting from the information stage, creative stage, analysis stage and development and recommendation stage. This study applies the Value Engineering method to the construction project of the Engineering Lecture Building 02 on Campus III of UIN Malang, focusing on the efficiency of construction costs in door, window, wall, and wall and floor finishing. Through the stages of information, creativity, analysis, development, and recommendations, as well as using Pareto analysis, profit-loss analysis, zero-one method, and life cycle cost analysis, an evaluation of alternative work is carried out. As a result, the initial cost Rp.78,474,577,233 if presented will result in savings of 3.676% of the total original budget. The savings are equivalent to a value of Rp. 945,446,805.74, As a supporting measure, a life cycle cost calculation was carried out for all stages of operation and maintenance, which shows that the implementation of this strategy resulted in savings of Rp.1,165.720.749 or 2,839%.